The yellow house mystery - Warner, Gertrude Chandler, 1890-1979 (Warner, Gertrude Chandler, 1890-1979. Boxcar children mysteries, 2023)
The Boxcar children are determined to solve the mystery that surrounds an old yellow house on their grandfather's property. Strange things have happened in that house where long ago a man disappeared.